1999
DOI: 10.1097/00000542-199912000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Epileptiform Electroencephalogram during Mask Induction of Anesthesia with Sevoflurane 

Abstract: Sevoflurane mask induction elicits epileptiform EEG patterns. These are associated with an increase in heart rate in patients with controlled hyperventilation and also during spontaneous breathing of sevoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(87 citation statements)
references
References 17 publications
5
75
0
7
Order By: Relevance
“…The halogenated anaesthetics sevoflurane, isoflurane and desflurane are thought to play an important role by altering the child's brain activity and upsetting the balance between central nervous system neuronal synaptic excitation and inhibition [5]. The incidence varies depending on the diagnostic criteria used, and although it is considered to occur with a relatively high frequency in children following sevoflurane anaesthesia, a recent review by Costi et al [6] found no difference in the incidence of emergence delirium following sevoflurane, desflurane or isoflurane.…”
Section: Editorialmentioning
confidence: 99%
“…The halogenated anaesthetics sevoflurane, isoflurane and desflurane are thought to play an important role by altering the child's brain activity and upsetting the balance between central nervous system neuronal synaptic excitation and inhibition [5]. The incidence varies depending on the diagnostic criteria used, and although it is considered to occur with a relatively high frequency in children following sevoflurane anaesthesia, a recent review by Costi et al [6] found no difference in the incidence of emergence delirium following sevoflurane, desflurane or isoflurane.…”
Section: Editorialmentioning
confidence: 99%
“…Kinder mit epilepsietypischen Potenzialen im EEG unter Sevofluran publiziert wurden [5,17], gab es kürzlich mehrere Berichte über das Auftreten von epilepsietypischer Aktivität bei Erwachsenen mit und ohne Epilepsieanamnese, bei denen Sevofluran verwendet wurde [4,10,11,15,18]. Im Folgenden möchten wir über eine Patientin berichten, die sowohl eine Propofol-als auch, bei einem weiteren Eingriff, eine Sevoflurannarkose erhielt.…”
Section: Nachdem Einzelne Fallberichte üBerunclassified
“…It is non-irritant, has a pleasant ethereal smell, and, with its low blood gas solubility of 0.6, induces anaesthesia rapidly. It also appears to have excitatory effect on the electroencephalogram (EEG) during inhalational induction (Yli-Hankala et al, 1999;Sato et al, 2002). It would appear to be a suitable agent for repeated induction of anaesthesia for short procedures, including ECT.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of sevoflurane on the electrophysiology of the brain has been studied, with conflicting results. Several workers have recorded epileptiform EEG tracings accompanied in some cases by visible motor manifestations (Yli-Hankala et al, 1999;Sato et al, 2002). The ability of sevoflurane to modulate neuroexcitability was shown in one study on patients with epilepsy to be dose-dependent, manifested most at near burst suppression doses of 1.5 minimum alveolar concentration (MAC).…”
Section: Discussionmentioning
confidence: 99%